Attributable length of stay and cost for pediatric and neonatal central line-associated bloodstream infections in Greece - Sofia Karagiannidou; Theoklis Zaoutis; Nikolaos Maniadakis; Vassiliki Papaevangelou; Georgia Kourlaba (Elsevier, 2019)
Background and objective: Central line-associated bloodstream infections (CLABSIs) are the most frequent pediatric hospital-acquired infections and are associated with significant morbidity and healthcare costs. The aim of our study was to determine the attributable length of stay (LOS) and cost for CLABSIs in pediatric patients in Greece, for which there is currently a paucity of data. Methods: A retrospective matched-cohort study was performed in two tertiary pediatric hospitals. Inpatients with a central line in neonatal and pediatric intensive care units, hematology/oncology units, and a bone marrow transplantation unit between June 2012 and June 2015 were eligible. Patients with confirmed CLABSI were enrolled on the day of the event and were matched (1:1) to patients without CLABSI (non-CLABSIs) by hospital, unit, and LOS prior to study enrollment (188 children enrolled, 94 CLABSIs). The primary outcome measure was the attributable LOS and cost. Baseline demographic and clinical characteristics were recorded. Attributable outcomes were calculated as the differences in estimates of outcomes between CLABSIs and non-CLABSIs, after adjustment for propensity score and potential confounders. Results: There were no differences between the two groups regarding their baseline characteristics. After adjustment for age, gender, matching characteristics, central line management after study enrollment, and propensity score, the mean LOS and cost were 57.5 days and €31,302 in CLABSIs versus 36.6 days and €17,788 in non-CLABSIs. Overall, a CLABSI was associated with a mean (95% CI) adjusted attributable LOS and cost of 21 days (7.3-34.8) and €13,727 (5,758-21,695), respectively. No significant difference was detected in LOS and cost by hospitalization unit. Conclusions: CLABSIs were found to impose a significant economic burden in Greece, a finding that highlights the importance of implementing CLABSI prevention strategies. Keywords: CLABSI, Bloodstream infection, Pediatric, Cost, Burden